Back to the Source: Moving Upstream in the Curricular Rivers of Coloniality. Issue 4 (December 2021) - James, Susan; Lorenz, Helene
This article shares choices made as part of an introductory decoloniality curriculum in a non-clinical community psychology M.A./PhD program where the authors are faculty members. We focus on the basics of decoloniality and decolonial pedagogies in two first-year foundational psychology courses: one course on implications of decoloniality for studying differing psychological paradigms, ontologies, and epistemologies, particularly relational ontologies that might reframe community environments, and another course on implications of decoloniality for post-humanist and indigenous qualitative research methodologies. We present currently emerging forms of theory, content, pedagogy, dialogue, artivism, and methodology in process in our work, as well as responses from students and our own reflections.